2019
DOI: 10.2174/2211738507666190319124513
|View full text |Cite
|
Sign up to set email alerts
|

Preparation, Optimization and In vitro Evaluation of Glipizide Nanoparticles Integrated with Eudragit RS-100

Abstract: Background: Solubility is an important criterion for drug efficacy, independent of the route of administration. It also poses a major challenge for pharmaceutical industries, which are developing new pharmaceutical products, since 40% of the active substances being identified are either insoluble or poorly soluble in aqueous media. Objective: The objective of this study was to develop nanoformulation of glipizide drugloaded nanoparticles providing controlled release formulation. Method: Nanoparticles were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 29 publications
1
8
0
Order By: Relevance
“…Average hydrodynamic diameter of microsphere formulation was evaluated using Zetasizer (Malvern Instruments, UK) and size found to be 0.5-0.6 µm that is within the range of microsphere size (0.5-1000 µm). This result is in good compliance with the findings by Saharan et al [23].…”
Section: Particle Size Analysissupporting
confidence: 94%
“…Average hydrodynamic diameter of microsphere formulation was evaluated using Zetasizer (Malvern Instruments, UK) and size found to be 0.5-0.6 µm that is within the range of microsphere size (0.5-1000 µm). This result is in good compliance with the findings by Saharan et al [23].…”
Section: Particle Size Analysissupporting
confidence: 94%
“…When the results obtained according to DDSolver criteria are examined; release kinetics of all formulations were fitted to Korsmeyer-Peppas model. Korsmeyer-Peppas model indicated that drug release followed a combination of diffusion as well as erosion mechanisms [8]. The n values of 0.280 and 0.212 for NP-1 and NP-2 coded NP formulation, respectively.…”
Section: In Vitro Release and Release Kinetic Evaluationmentioning
confidence: 95%
“…Many polymers with natural or synthetic origin are used in the production of NPs. One of the synthetic ones is Eudragit RS 100 (ERS) [8]. ERS is a co-polymer of poly (ethyl acrylate, methyl-methacrylate, and chloro-trimethyl-ammonio-ethyl methacrylate).…”
Section: Introductionmentioning
confidence: 99%
“…BH can not only be adsorbed on the surface of Mt but also be exchanged with intercalated Na + to generate Mt-drug complex (Mt-BH) carriers (Zhao et al, 2019 ). Eudragit polymers are a type of ammonium methacrylate copolymer with permeabilities and release parameters that can be conveniently adjusted by changing the proportions of the Eudragit RS/RL mixtures (Singh et al, 2011 ; Saharan et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%